Sementes de soja tratadas com formulações de biorreguladores - Balduino, Ana Carolina Campos (2021)
The soybean is a crop of high economic importance for the world, being one of the most exported agricultural products from Brazil, and to meet this demand each year the soybean farming has achieved high productivity using technologies such as seed treatment with bioregulators. Therefore, the objective was to evaluate the physiological quality of soybean seeds treated with different formulations containing bioregulators, and to verify how the use of these substances via seed treatment affects the development of soybean seedlings. The experiment was conducted in the city of Rondonópolis-MT in the seed laboratory of the Federal University of Rondonópolis, and in the greenhouse of the company Fast Agro. In the vegetation house the seeds were distributed in sand substrate and the evaluation was performed seven days after sowing, quantifying the germination percentage, emergence speed index and dry matter of the aerial part. In laboratory, the seeds were placed on paper substrate, 3 days after sowing, as normal seedlings, they were evaluated for total length, shoot and root, dry matter of shoot, root and total. The germination parameter was also obtained in percentage. For the experiments the soybean cultivar TMG-2185 IPRO was used and the treatments were organized into 25 formulations of bioregulators, each formulation containing different concentrations of kinetin, gibberellic acid, AIB, and substance S (confidential), a control and a formulation C (confidential). The experimental design entirely randomized with 27 treatments and 4 repetitions. The bioregulator applied via seeds increased the vigor of soybean seedlings showing positive effects on their development and significant increases in the variables seedling length and dry matter for products 9 (0.001 g of kinetin; 0.001 g of gibberellic acid; 0.001 g of IAB; and 0.3 g of substance S), 18 (0.004 g of kinetin; 0.002 g of gibberellic acid; 0.002 g of IAB; and 0.2 g of substance S), 21 (0.002 g of kinetin; 0.002 g of gibberellic acid; 0.00 g of IAB; and 0.2 g of substance S), and 26 (substance C). It was concluded that the tested bioregulators did not interfere in the germination of seeds, product 12 (0.003 g of kinetin, 0.003 g of gibberellic acid, 0.001 g of AIB, and 0.3 g of substance S) presented inhibitory effect on the growth of the root system, treatment 26 composed of formulation C was the bioregulator that most benefited the development of seedlings, product formulation 19 composed of 0, 002 g of kinetin, 0 g of gibberellic acid, 0.002 g of AIB and 0.2 g of substance S reduced the percentage of emergence and the rate of emergence of seedlings, and that the concentration of substance S of 0.3 g in the formulation of products 10, 11, 13, 16 and 0.2 g in products 18, 19, 20, 21, and 22, provided greater root length of soybean seedlings cultivar TMG-2185 IPRO.